Panorama de hackathons no Brasil - Rodrigues, Renato Tadeu (2019)
Open innovation practices promoted by Brazilian companies have gained prominence since the year 2014. This is related to the new dynamics of the world economy, driven mainly by the technological revolution and the popularization of the Internet. Conse-quently, a market is born for digital products like applications, software and hardware. In this scenario, open innovation events, known as hackathons, became popular. The present study has as general objective to analyze the reasons for Brazilian organiza-tions to perform hackathons and to identify what is done with the winning products after the event. Exploratory and of a qualitative nature, the research used case studies to achieve its objectives. We interviewed six companies that promoted hackathon events with different themes, but related to the process of digital innovation, three consultan-cies that work in the organization of hackathon and twenty individuals participating in the marathons on a voluntary basis. Among the main answers, it was observed that the events have as benefits: the improvement of the image of the organization vis-à-vis society and its stakeholder (when confronting respondents' answers); supporting the development of an organizational culture focused on innovation and the retention of new creative collaborators. Participants cite as advantages, the expansion of the network of relationships with companies and other hackathon agents, the exchange of skills and the possibility of contributing to social causes. One of the difficulties pointed out is the lack or direction of support for the implementation of the projects, since there is no post-hackathon. There are relatively few winning projects properly implemented after the event, as the researcher observed in the search for cases to illustrate the projects that continued. Problems related to infrastructure, intellectual property and the organization of marathons have also been reported.